Effects of environmental factors on the species composition of aquatic insects in irrigation ponds. Issue 2 (12th July 2013) - Nakanishi, Kosuke; Nishida, Takayoshi; Kon, Masahiro; Sawada, Hiroichi
Abstract Although irrigation ponds contribute to the conservation of aquatic biodiversity, they have experienced declines in recent years. We therefore examined the relationships between various environmental factors and the community composition of aquatic insects, specifically insect predators, in irrigation ponds to gain knowledge that would aid in the conservation and restoration of biodiversity. We selected Odonata, Hemiptera and Coleoptera as target taxonomic groups and conducted censuses of these groups in 21 ponds in Shiga, central Japan. In total, we collected 30 and 10 species (or species groups) of Odonata and Hemiptera, respectively, and 17 species of Coleoptera. A partial canonical correspondence analysis revealed that the following four environmental factors significantly affected the species composition of aquatic insect communities: the number of emergent plant species, percent concrete revetment, presence of litter and peripheral length. Among these variables, the number of emergent plant species was the most potent factor, perhaps because emergent plants serve as sites for oviposition and emergence, and provide refugia for aquatic insects (odonate nymphs in particular). In contrast, some species specifically inhabited sites poor in emergent plants. This study shows that reductions in concrete revetments are necessary for the conservation of biodiversity. This would lead to increases in the number of aquatic plant species, which provide habitats and oviposition sites for many aquatic insects. Furthermore, to enrich the local biodiversity of aquatic insects, groups of irrigation ponds with different environments are needed.